On the Determination of Coordination Numbers of Coupled DEM-DFN Model for Modeling Fractured Rocks - Xu, Xiaoyi; Fu, Li-Yun; Liu, Ning; Han, Tongcheng (Frontiers in Earth Science, 2021)
Natural fractured rocks usually contain background granular media and multi-scale fractures. The coordination number is a crucial factor to characterize the connection of microstructural elements. The determination of coordination numbers for modeling fractured rocks is essential to interpret the distribution of cracks related to micromechanical properties. We have built a consistent workflow of discrete element models (DEMs) coupled with discrete fracture networks (DFNs). This DEM-DFN model could provide a simple formulation for high calculation efficiency to model a more realistic and detailed description of fracture system. A series of numerical experiments are set up, aiming to correlate window radius, particle size, and crack length, which will benefit the window selection for measuring coordination numbers based on the crack characteristics. The coordination number determined in the DEM-DFN modeling can be used to identify crack patterns in the spatial distribution.